Construction and practice of big data fundamental ability for telecom operators - Jinsong TANG; Yun CAI; Xiaoliang WANG; Yiping FU; Xiaowei TANG; Yonggang CHEN; Ting ZHANG (Dianxin kexue)
Take Zhejiang Mobile as an example,the big data capability was demonstrated from three aspects:platform,data and technology.Combined with the enterprise practice and exploration,industry cases were shared in terms of credit score and site selection.